Examining the Mental Health, Wellbeing, Work Participation and Engagement of Medical Laboratory Professionals in Ontario, Canada: An Exploratory Study - Nowrouzi-Kia, Behdin; Dong, Jingwen; Gohar, Basem; Hoad, Michelle (Frontiers in Public Health, 2022)
Objectives: The overall objective of this proposed project is to examine the impact of the COVID-19 pandemic on the mental health, functioning and well-being of medical laboratory technologists (MLT) and medical laboratory technicians/assistants (MLT/A) in Ontario, Canada. Methods: A cross-sectional study included a questionnaire for MLT and MLT/A in Ontario. The questionnaire included questions about mental health, functioning, well-being and psychosocial work environments, roles and demographics, and occupational characteristics using validated questionnaires. Descriptive statistics were used to profile the characteristics of the sample. Results: There were 551 MLT and 401 MLT/A in the analytic sample. Most of the respondents were women. The mean age and standard deviation of the overall sample were 42.0±11.8. MLT demonstrated higher quantitative demands, possibilities for development, and organizational justice as than MLT/A. The scores of work pace, emotional demands, role conflicts, job insecurity, insecurity over working conditions and negative acts were higher for MLT/A than MLT. The WHODAS 2.0 scores of the respondents were 20.80±6.68, higher than approximately 92% average people. For both groups, the majority of the respondents reported worse feelings across the COPSOQ III domains since COVID-19. Conclusions: Mental health, functioning and disability, were significant health concerns for medical laboratory professionals in Ontario. Accordingly, it is necessary to pay more attention to these health problems among medical laboratory professions.